A prospective, split-face, randomized controlled trial of intense pulsed light-photodynamic therapy for seborrhea - Dixin Wang; Yu Yan; Peiru Wang; Haiyan Zhang; Yajing Cao; Bo Wang; Linglin Zhang; Xiuli Wang (Photodiagnosis and Photodynamic Therapy)
Background: Seborrhea poses a common cosmetic concern in adolescents and young adults, often accompanied by enlarged pores, and contributing to various skin conditions, including acne vulgaris and seborrheic dermatitis. At present, there is a lack of effective treatment for this problem, and the potential of photodynamic therapy (PDT) in reducing sebum remains inconclusive. Objective: This exploratory, prospective, single-center, double-blinded, randomized split-face controlled trial aimed to compare the efficacy and safety of intense pulsed light-photodynamic therapy (IPL-PDT) versus IPL therapy for seborrhea. Methods: Participants with seborrhea underwent 3 times of IPL treatment (590 nm, 15–17 J/cm2 based on patient's tolerance) for one hemifacial part and IPL-PDT treatment for the other. Follow-up assessment was conducted up to 8 weeks after the final treatment. Results: Compared with single IPL treatment, IPL-PDT can significantly inhibit sebum secretion and decrease pore size. PDT group exhibited no additional damage to the skin barrier, with even lower transepidermal water loss (TEWL). Additionally, the PDT group showed superior improvement in scores of porphyrins, red areas, and ultraviolet (UV) spots. Both groups experienced only mild topical adverse effects, well tolerated by the participants. Conclusion: IPL-PDT is a more effective method than IPL in the treatment of seborrhea, as well as on the improvement of the skin barrier function.